2007
DOI: 10.1111/j.1365-2702.2007.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Living kidney organ donation: experiences of spousal support of donors

Abstract: The substantive theory of 'Fulfilling Your Vows' will guide nurses and other transplant specialists in helping to improve fully informed consent of potential donors before surgery and in developing supportive strategies to maximize spouse, donor and family outcomes throughout the transplantation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…However, male spouses and caregivers of living donors had all accessed the Internet seeking information about living kidney donation. 21 …”
Section: Development Of the Living Donor Information Network For Carementioning
confidence: 99%
See 2 more Smart Citations
“…However, male spouses and caregivers of living donors had all accessed the Internet seeking information about living kidney donation. 21 …”
Section: Development Of the Living Donor Information Network For Carementioning
confidence: 99%
“…In 2 studies 21,38 of living kidney donors, donors reported unexpected financial hardships related to the donation. In another pilot study, 24 35% (n=52) reported that recovery from surgery was more painful than they had anticipated.…”
Section: Development Of the Living Donor Information Network For Carementioning
confidence: 99%
See 1 more Smart Citation
“…Patients suffering from chronic kidney disease who stand to benefit from transplantation have steadily risen over the last two decades and renal transplantation has long been considered an acceptable and popular operation as the "last" option for someone who is suffering from end-stage organ failure (Iglesia-Marquez, et al, 2001;Waterman, et al, 2004;Wright, Richardson & Grant, 2004;Stothers, Gourlay & Liu, 2005;Taylor & McMullen, 2007;Symvoulakis, Stavroulaki, Morgan & Jones, 2010). The numbers of transplants derived from living kidney donors is rising steadily (Horvat, 2009;VanGelder, et al, 2009;Excell, 2010;Transplant Living, 2010), but the thorny issue remains and it is unclear whether the conflict of benefiting one patient by potentially harming another has been fully rectified.…”
Section: Primum Non Nocere: First Do No Harmmentioning
confidence: 99%
“…2 Such information may help the healthcare team in obtaining informed consent from future donors, promoting the well being of donors and their families, and possibly infl uencing the decision of others considering kidney donation. The aim of this study was to determine the overall experience (assessment, procedure, and post-operative course) of kidney donors and to obtain their feedback about the service at our center.…”
mentioning
confidence: 99%